ANALISIS KESALAHAN PENGUCAPAN DALAM PEMBELAJARAN BAHASA INGGRIS DI KELAS VII SMP PEMETUNG (PENDEKATAN LINGUISTIK TERAPAN) - Muklas, M.; Sugiarti, Sugiarti; Suryani, Mita Puji; Alawy, Faiz (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research aims to analyze pronunciation errors in English learning in class VII Pemetung Middle School using an applied linguistics approach. This research used an observation method on class VII students at Pemetung Middle School. Observations were carried out to identify pronunciation errors that often occur. Data was collected from direct observation and then analyzed using applied linguistics concepts. The results of the study showed that there were various pronunciation errors made by class VII students at Pemetung Middle School. Some of the most common errors involve errors in pronunciation of consonants, vowels, as well as intonation. These errors are often caused by the influence of a student's native language or the influence of social media influencing the way they speak English. An applied linguistics approach is used to design learning strategies aimed at correcting these pronunciation errors. By applying this approach, students are taught how to use English phonological rules and are given special exercises to improve their pronunciation. This research contributes to the understanding of pronunciation errors in English learning at Pemetung Middle School and provides concrete solutions to improve students' ability to speak English correctly. In addition, this research also provides a more in-depth view of the application of the applied linguistics approach in teaching English in secondary education environments.